2011
DOI: 10.1186/1471-2180-11-97
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide expression profiling of the response to short-term exposure to fluconazole in Cryptococcus neoformans serotype A

Abstract: BackgroundFluconazole (FLC), a triazole antifungal drug, is widely used for the maintenance therapy of cryptococcal meningoencephalitis, the most common opportunistic infection in AIDS patients. In this study, we examined changes in the gene expression profile of the C. neoformans reference strain H99 (serotype A) following FLC treatment in order to investigate the adaptive cellular responses to drug stress.ResultsSimultaneous analysis of over 6823 transcripts revealed that 476 genes were responsive to FLC. As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
39
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 53 publications
6
39
0
2
Order By: Relevance
“…3B). We compared published work that examined the transcriptome responses of S. cerevisiae (Kuo et al, 2010) and C. neoformans (Florio et al, 2011) to FLC. We found that, while there was significant overlap in orthologous genes impacted in the two species, (p = 1.6 × 10 −3 ), there were also considerable differences: 67% of the genes with an altered response in C. neoformans whose orthologs in S. cerevisiae did not exhibit significant change, (Table S7) (Kuo et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3B). We compared published work that examined the transcriptome responses of S. cerevisiae (Kuo et al, 2010) and C. neoformans (Florio et al, 2011) to FLC. We found that, while there was significant overlap in orthologous genes impacted in the two species, (p = 1.6 × 10 −3 ), there were also considerable differences: 67% of the genes with an altered response in C. neoformans whose orthologs in S. cerevisiae did not exhibit significant change, (Table S7) (Kuo et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Comparison of transcriptional response to FLC in S. cerevisiae (Kuo et al, 2010) and C. neoformans (Florio et al, 2011). Related to Fig.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…Furthermore, incubation with sub-inhibitory concentrations of fluconazole caused C. albicans to upregulate oxidative stress response genes and made the organism more resistant to killing by phagocytes [36]. Exposure to sub-inhibitory concentrations of fluconazole had a similar affect on C. neoformans [37]. Oxidative stress has also been postulated to be involved in the synergy of compounds with the azoles.…”
Section: Discussionmentioning
confidence: 99%
“…Sage was used in Cryptococcus to examine the transcriptome changes in response to temperature and iron concentration manipulations (Hu et al, 2008; Steen et al, 2002). Recently, progress in transcriptional techniques has allowed researchers to analyze gene expression profiling changes to antifungal drugs, iron depletion, CO2 and oxidative stress by DNA microarray analysis in Cryptococcus (Florio et al, 2011; Kim et al, 2010; Upadhya et al, 2013). These microarray analytic techniques have resulted in the identification of new transcription factors and regulatory proteins in signaling pathways (Chun et al, 2011; O'Meara et al, 2010).…”
Section: Genome-wide Analysismentioning
confidence: 99%